Naravna konvekcija v vodoravnem valju - Mohorič, Aleš (Obzornik za matematiko in fiziko, 2010)
The article describes a basic model of natural convection in cylindrical geometry. We solve the coupled system of dynamical and thermodynamical equations describing a liquid by truncating the Fourier series. The solutions of the simplified system tend toward the Lorenz attractor in phase space for large enough temperature gradients. The numerical solutions offer an insight into the order of temperature, flow, and characteristic time, typical for convection in a closed container.
Keywords: difuzija; geometrija; konvekcijski tok; naravna konvekcija